Role of Incentives on Teachers’ Performance in Eastern Division Tororo Municipal Council - Dismas Ikemer (Uganda Christian University, 2024)
The study determines the contribution of incentives on teacher’s performance in primary and secondary schools in Eastern division Tororo municipal council. The study was supplemented by research objectives which included establishing the contribution of teacher promotion performance in Eastern division Tororo Municipal Council assessing the contrition fringe benefits on teacher’s performance in Eastern division Tororo municipal council. The study used descriptive research design and the case study of Eastern division Tororo Municipal Council to achieve the set objectives the study used simple random sampling and purposive sampling in sample selection. A sample of 65 respondents was selected which comprised of head teachers, teachers school management committees opinion leaders PTA member s among others the study findings revealed that equality of life of employee is improved, attainment of skilled employee is made possible over other companies, a sense of belonging among is realized. Fraud and embezzlement of fund is minimized t through fringe benefits, recognitions in an organization is exercised and organization performance is improved. In addition, the findings revealed that development of new skills is attained, performance appraisal is the key factor during promotion, and lack of qualified promoters affect promotion exercise, they are encouraged to attain organizational goals. On the other hand, the effect of salary on employee performance, employee commitment and hard work, good relationship between employee and employers, it creates confidence in the organization by the stack holders and it leads to high quantity and quality of output. Conclusively the research revealed that the employees are trained, improvement in skills, quality output attained, efficiency and effectiveness, fraud and embezzlement of fund was minimized and good working relationship among staff and top management. The researcher recommends that the authorities should continue to train its staff, carryout mentorship programs, encourage teamwork, motivation and carry out training across all departments.
Undergraduate research